Comparing the Nambu-Goto string with LGT results - Caselle, M.; Hasenbusch, Martin; Panero, Marco (Journal of high energy physics, 2005)
We discuss a way to evaluate the full prediction for the interquark potential which is expected from the effective Nambu-Goto string model. We check the correctness of the prescription reproducing the results obtained with the zeta function regularization for the first two perturbative orders. We compare the predictions with existing Monte Carlo data for the (2+1) dimensional Z(2), SU(2) and SU(3) gauge theories: in the low temperature regime, we find good agreement for large enough interquark distances, but an increasing mismatch between theoretical predictions and numerical results is observed as shorter and shorter distances are investigated. On the contrary, at high temperatures (approaching the deconfinement transition from below) a remarkable agreement between Monte Carlo data and the expectations from the Nambu-Goto effective string is observed for a wide range of interquark distances.